GAMBARAN RISIKO PENYAKIT KARDIOVASKULAR PADA PEKERJA KANTORAN DALAM DUA DEKADE MENDATANG - Astari, Ni Made Winda; Suarningsih, Ni Kadek Ayu; Prapti, Ni Ketut Guru; Nurhesti, Putu Oka Yuli (Coping: Community of Publishing in Nursing, 2024)
Cardiovascular disease is a major contributor to reduced quality of life and disability, with cases increasing every year. Cardiovascular disease has a long asymptomatic period, so prevention and control programs are very important, one of which is through disease risk assessment. This study aimed to identify the risk of cardiovascular disease in office workers in the next two decades. This research used a descriptive quantitative method with a cross-sectional approach and was conducted in one of the banks located in Gianyar Regency. The sample of this study was 30 employees who were selected using the probability sampling technique, which is total sampling. This study consists of anthropometric measurements and cardiovascular disease risk assessment using the Healthy Heart Score questionnaire, which focuses on assessing nine lifestyles that are known to be most effective in assessing cardiovascular disease risk. The results of the analysis showed that 46,7% of respondents had a high risk of cardiovascular disease in the next two decades and the other 40% had a moderate risk. Furthermore, lifestyle analysis revealed the majority of respondents did not consume fruit and vegetables as suggested (76,7%), most consumed sweetened drinks (67,3%), half did not engage in physical activity (50%), and half regularly consumed alcohol (50%) in the previous year. It can be concluded that most respondents have a high risk of cardiovascular disease in the next two decades assessed based on their lifestyle.